Level Of Patient Knowledge On The Use Of Dentures After Permanent Tooth Extraction At Molawe Health Center, North Konawe Regency - Utari; arsad; Rezki Dirman; Dewi Lidiawati; Indirwan (Sahabat Publikasi Kuu, 2025)
Dental health is an integral part of health in general. Maintaining dental health is important. Teeth that are not cared for or maintained in health and hygiene can damage teeth such as caries, periodontal disease, and fractures when traumatized. Therefore, if the tooth is left in such a state, it can potentially lose the tooth. Dentures are prostheses that replace some or all of the missing natural teeth and surrounding tissues. The use of dentures can be influenced by several factors such as the high cost of making dentures, the length of time it takes to make dentures and the lack of public knowledge about the benefits of using dentures. The purpose of the study was to determine the level of knowledge of patients about the use of dentures after permanent tooth extraction at the Molawe Health Center based on gender, age, education, occupation and income. This study is a descriptive research with a cross sectional approach using the total sampling technique and the number of samples as many as 37 respondents. The results showed that the relationship between knowledge level and gender was obtained with a p-value of 0.473, the relationship between knowledge level and age was obtained with a p-value of 0.023, the relationship between knowledge level and education was obtained with a p-value of 0.000, the relationship between knowledge level and employment was obtained with a p-value of 0.004, and the relationship between knowledge level and income was obtained with a p-value of 0.005. This study shows that there is no relationship between the level of knowledge and gender on the use of dentures after tooth extraction. Furthermore, there is a relationship between the level of knowledge and age, education, occupation, and income on the use of dentures after tooth extraction.